2019
DOI: 10.1136/bmjopen-2018-026711
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vestibular rehabilitation, with or without betahistine, on managing residual dizziness after successful repositioning manoeuvres in patients with benign paroxysmal positional vertigo: a protocol for a randomised controlled trial

Abstract: IntroductionBenign paroxysmal positional vertigo (BPPV) is recognised as the leading cause of peripheral vertigo in adults. The canalith repositioning procedure (CRP) can be used for effective treatment of BPPV. However, some patients experience residual dizziness (RD) even after successful CRP, resulting in a significant negative impact on their daily function and quality of life. Exercise-based vestibular rehabilitation (VR) has been proven as an effective method for managing dizziness and has been applied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…Although RD is mostly a self-limiting condition, patients can sometimes develop enough discomfort and disabling symptoms to require physical treatment and vestibular rehabilitation, in combination with medications if needed [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although RD is mostly a self-limiting condition, patients can sometimes develop enough discomfort and disabling symptoms to require physical treatment and vestibular rehabilitation, in combination with medications if needed [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several medications have been proposed to approach RD, but nothing has yet been proven to provide relief for this disorder compared to placebo [ 13 ]. Albeit with conflicting results, the most commonly used molecule to approach RD is betahistine [ 22 , 24 , 31 ]. According to a randomized controlled trial, dimenhydrinate is a vestibular suppressant that could help prevent RD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RD is associated with significant anxiety, disabling dizziness even after the resolution of the acute vertigo and in the absence of otolithic or vestibular dysfunction. 1 The cause of RD remains unknown, but it has been proposed that otolith dysfunction or co-existing vestibular disease may lead to incomplete central adaptation. The movement of otoconia, returning to the utricle, has also been postulated to be the cause of RD after CRP.…”
Section: Residual Dizziness After Repositioning Maneuvers In Bppvmentioning
confidence: 99%
“…The reported prevalence of BPPV is about 10.7-64 per 1,00,000 people, and BPPV has a lifetime prevalence of 2.4%. 1 A multicenter study conducted in India reported that BPPV accounted for a considerable percentage of the overall burden of vertigo. It was reported that peripheral causes were predominant in majority of patients (74%), with BPPV being the most frequent (68%).…”
Section: Introductionmentioning
confidence: 99%